Application of Structural Elements of the Homosapienspsychein Artificial Intelligence Architecture - Kruglov, A. G.; Kruglov, A. A. (Transactions on Engineering and Computing Sciences, 2025)
By utilizing the sensory channels, the psyche of biological organisms forms a mirror-like symmetrical information space of the reflected external environment. The symmetry line is the polymorphic sensory field of the organism's extra/interoception. The fundamental principle of functioning of the psyche of biological organisms is the creation and maintenance of a systemic homeostatic/informational equilibrium. The HS psyche has evolutionarily formed mental regulatory algorithms, which have acquired the ability to translate/interfere properties and meanings between phenomena/objects of various species, expanding the communicative and intellectual potential of HS, in comparison with other biological species. Algorithmically repeating organized frequency patterns of the external environment, perceived outside the focus of voluntary attention and creating an arsenal of "hidden regulatory algorithms" (HRAs). Upon updating HRAs are perceived as manifestations of “intuition” or “emerging abilities.” Extrapolation of the AIarchitecture to the psyche of Homo Sapiens with autism spectrum disorders (ASD) has shown significant similarity in the structural principles of these intelligent systems. One of the main problems of ASD/AI is the impossibility of constructing mental RAs of communicative/social vectors with "blurred" parameters of the goal image. Under the traditional approach, this problem is also relevant for AGI programming. We consider the use of structural blocks of hieroglyphic thinking to be a promising direction for integrative AGI architecture. Originating from pictographic writing, the hieroglyph graphically (visually) conveys the general, complete idea ofan object/phenomenon/concept. The constructive difference between hieroglyphic thinking and conceptual thinking consists in the reduction of abstraction, metaphor, and uncertainty in the mental regulatory algorithms of the communicative and social spectra, which implies effectiveness in AGI architecture.